Gambaran Tinggi Badan Anak Umur 0-36 Bulan Di Desa Banyu Irang Kecamatan Bati Bati Kabupaten Tanah Laut Tahun 2013 - Nina Rahmadiliyani; Rusman Efendi; Pujiah Pujiah; STIKES Husada Borneo; Puskesmas Bati-Bati Kabupaten Tanah Laut (Jurnal Kesehatan Indonesia, 2014)
Ministry of Health, 2010 declare, besides of malnutrition, there are a lot of problems related nutritions that need more attention, they are; stunting or inhibition of body growth. Stunting is one form of malnutrition which is characterized by body length according to the age measured by WHO anthropometric standard. WHO data shows that Indonesian’s Children body length still left behind than childrens body length from another countries. Tanah laut health profile reports that prevalences of malnutrition in 2011 as 19,9% and short toddlers as 20%, very short as 8%. Bati-bati health center work area in 2012 obtained data nutritional status monitoring malnutrition as 13,9%, short 18,2%, and very short 7,8%. This research is to find the description of girls and boys body length for-age 0-36 month in banyu irang village year 2012. The type and design of the study was a discriptive,using toddler chart. Results, boys 0-36 month has a very short bodies as 4 peoples (5,5%) and short 9 peoples (12,3%), while the girls 0-36 months wich has very short bodies as 6 peoples (10%) and short 9 peoples (14,7%). The result of median anthropometric standard describe that the growth of girls body length for-age 0-36 months shows the pattern of growth is under the median standard line compared than boys median standard 0-36 monthsare mostly aligned with anthropometric median. The pattern of boys body length growth for-age 0-36 months is more stable when compared with the girls in banyu irang village bati-bati distrcit year 2012.